2014
DOI: 10.1002/2013jd021064
|View full text |Cite
|
Sign up to set email alerts
|

CMIP5 model simulations of the impacts of the two types of El Niño on the U.S. winter temperature

Abstract: Thirty Coupled Model Intercomparison Project phase 5 (CMIP5) preindustrial simulations are examined to contrast impacts of the two types of El Niño on the U.S. winter temperatures. The CMIP5 models are found more capable of simulating the observed eastern Pacific (EP) El Niño impacts (a warm northeast, cold southwest pattern over the U.S.) but less capable of simulating the observed central Pacific (CP) El Niño impacts (a warm northwest, cold southeast pattern). During EP El Niño, sea surface temperature (SST)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…The discrepancy between our reconstruction and the simulations can be ascribed to general deficiencies still affecting the simulated representation of key chemical and physical processes related to aerosol forcing, and to the consequent large uncertainties in the simulated climate response to volcanic forcing 25,36 . Further possible explanations are the common model deficiencies concerning regional precipitation variability at the decadal and multi-decadal time ARTICLE scales 37 , which are linked to poor and hence less robustly simulated representation of dominant modes of large-scale climate variability and associated teleconnections including ENSO 38 and the AMO 39 . Large uncertainties also affect the reconstructed forcing 40 and we have very limited knowledge about the background climate conditions at the time of volcanic eruptions that occurred before the last half of the twentieth century 30 .…”
Section: Resultsmentioning
confidence: 99%
“…The discrepancy between our reconstruction and the simulations can be ascribed to general deficiencies still affecting the simulated representation of key chemical and physical processes related to aerosol forcing, and to the consequent large uncertainties in the simulated climate response to volcanic forcing 25,36 . Further possible explanations are the common model deficiencies concerning regional precipitation variability at the decadal and multi-decadal time ARTICLE scales 37 , which are linked to poor and hence less robustly simulated representation of dominant modes of large-scale climate variability and associated teleconnections including ENSO 38 and the AMO 39 . Large uncertainties also affect the reconstructed forcing 40 and we have very limited knowledge about the background climate conditions at the time of volcanic eruptions that occurred before the last half of the twentieth century 30 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, what causes the TNH pattern to stay in its positive phase for an extended period of time? Previous studies have suggested the TNH (or TNH-like) pattern may be triggered by tropical forcing mechanisms, such as the El Niño (Mo and Livezey 1986;Barnston et al 1991;Yu et al 2012;Yu and Kim 2011;Yu and Zou 2013;Zou et al 2014), the quasi-biennial oscillation (Barnston et al 1991), the propagation of the wave activity initiated from the western tropical Pacific Ocean (Wang Lee et al 2015;Seager and Henderson 2016;Hu et al 2017), and the internal dynamics in the atmosphere (Kumar et al 2013;Seager et al 2014;Xie and Zhang 2017). Also, recent warming in the Arctic regions has been suggested to exert strong impacts on midlatitude weather and climate by altering large-scale atmospheric circulation patterns (Cohen et al 2012(Cohen et al , 2014Kim et al 2014;Peings and Magnusdottir 2014;Deser et al 2015;Lee et al 2015;Overland et al 2015Overland et al , 2016Yu et al 2017).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…As a result, the equatorial Pacific is observed to display a minimum sea surface temperature (SST) extending from the coast of South America to the central Pacific, commonly referred to as the cold tongue (Wyrtki 1981;Xie 2013). It is well known that large interannual SST anomalies of the equatorial Pacific cold tongue associated with El Niño-Southern Oscillation (ENSO) have considerable effects on the regional and global climate, such as the Indian summer monsoon (ISM; Webster and Yang 1992;Kumar et al 1999;Wu et al 2012), East Asian climate (e.g., Wang et al 2000;Zhou and Wu 2010;Yang et al 2014), north Asian climate (e.g., Ropelewski and Halpert 1986;Larkin and Harrison 2005a;Zou et al 2014), and global sea level pressure (SLP), surface temperature, and precipitation (e.g., Ropelewski and Halpert 1987;Kiladis and Diaz 1989;Klein et al 1999;Trenberth and Caron 2000;Alexander et al 2002;Larkin and Harrison 2005b;Banholzer and Donner 2014).…”
Section: Introductionmentioning
confidence: 99%